Avaliação da influência do alinhamento pélvico sobre a postura de tronco e ombro e sobre a atividade eletromiográfica de rotadores superiores da escápula - Barbara Alice Junqueira Murta (2015)
Introduction: The position of a segment can be influenced by changes in alignment of non-adjacent segments and may be related to the muscular activation pattern required to produce a particular motion. In this context, modification of pelvic alignment could promote a reduction in shoulder protrusion (SP) due to the relationship among shoulder, scapula and spinal alignment and the relationship between spinal and pelvic alignment. Furthermore, a change in shoulder alignment, resulting from changes in pelvic alignment, could alter the electromyographic (EMG) activity of the upward rotators of the scapula during shoulder abduction and adduction. Objective: To investigate the effect of reducing anterior pelvic tilt on trunk posture, SP, and the activation of the scapular upward rotators during abduction and adduction of the shoulder. Materials and methods: 31 young adults were submitted to evaluation of pelvic tilt, anterior displacement of the pelvis (antepulsion), trunk extension and SP in the static posture and of EMG activity of the scapular upward rotators during abduction and adduction of the shoulder. Measures were performed under two conditions: orthostatic posture with habitual pelvic alignment and after active 30% reduction of the anterior pelvic tilt, determined by means of an inclinometer placed on the sacrum. Initially Paired t tests were used to compare the two pelvic tilt variables (sacral slope and pelvic tilt) between the study conditions and the percentage of sacral inclination reduction was calculated. In addition, a Pearson correlation test was used to evaluate the correlation between the two measures of pelvic tilt. Paired t tests were also used to verify the effect of pelvic manipulation on the linear movement of the pelvis and the trunk and shoulder alignment. Analyses of variance (ANOVAS) with two repeated measure factors (movement phase and study condition) were used to evaluate the effect of the manipulation of the pelvis on the EMG activity of scapular upward rotators. Results: The results confirmed that the manipulation of the pelvis was performed as proposed. Regarding the correlation between the two measures of pelvic tilt, a moderate correlation was found (r = 0.59). No effect of active manipulation of the pelvis on the SP and the EMG activity of the upper trapezius (UT) and anterior serratus (AS) was found. However, manipulation of pelvic alignment promoted a reduction in the antepulsion, trunk extension and an increase in lower trapezius activity (LT) in the two movement phases. A phase effect for the UP, AS and LT was also found, indicating lower magnitude of activation of the three muscles in the eccentric phase (i.e. adduction). Discussion and Conclusion: Despite the best trunk alignment with respect to the vertical obtained with the proposed manipulation, no effect on shoulder alignment was observed. It is possible that this lack of effect of pelvic position on shoulder alignment was influenced by a probable lack of alignment change in the thoracic region. The reduced extension of the trunk appears to be related to the increased LT activity since, even in the absence of the shoulder position modification, it was found an increased activity of this muscle, not observed in the UT and AS. The influence of the pelvis alignment on the shoulder posture should not be disregarded because of a possible influence of thoracic segment in the relationship between shoulder-trunk-pelvis.